Lesson study in field practice: a time-lagged experiment in initial teacher education in Norway. Issue 2 (11th April 2016) - Munthe, Elaine; Bjuland, Raymond; Helgevold, Nina
Abstract : Purpose: – The purpose of this paper is to describe the background for, the design of, and the implementation of Lesson Study in a teacher education program in Norway. Lesson Study was chosen as an intervention in an attempt to shift pre-service teachers' focus from themselves to their pupils, attempting to strengthen their possibilities to learn more about the consequences of their instructional decisions for their pupils. Design/methodology/approach: – The study used a time-lagged experiment where one group of second year pre-service teachers took part in their three-week field practice as usual (business-as-usual-condition), and one group, the following year, took part in Lesson Study cycles during their three-week field practice period. The students were recruited from four subject areas in both conditions: Math, Physical Education, Science, and English. Findings: – The use of Lesson Study created more collaborative inquiry among the pre-service teachers. At its best, the pre-service teachers formulated research questions, took active part in observations, and used data (pupils' work, interviews and observations) to inform their choices about how to create improved learning for their pupils. Research limitations/implications: – The study is a small scale study due to the need to test before upscaling. Practical implications: – The paper includes a description of how Lesson Study was implemented in a Teacher Education Department, and this can be valuable information for others who are attempting the same. Originality/value: – This paper fulfills an identified need to learn more about pre-service teachers\ learning and lesson study in teacher education.